2023
DOI: 10.1002/aaai.12077
|View full text |Cite
|
Sign up to set email alerts
|

Toward AI assistants that let designers design

Abstract: We need to rethink how we assist designers with artificial intelligence (AI). AI should aim to cooperate, not automate, by supporting and leveraging the creativity and problem-solving capabilities of designers. The challenge for such AI is how to infer designers' goals and then help them without being needlessly disruptive. We introduce AI-assisted design, a new framework for creating such AI, built around generative user models, which allow it to infer and adapt to designers' goals, reasoning, and capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…These include generative design tools, data-driven approaches, and artificial intelligence (AI) tools such as ChatGPT and Google Bard [19]. Generative design tools use algorithms to generate a large number of design options, which are based on predefined rules and constraints [20]. Data-driven approaches use user data and feedback to guide ideation and design decisions [21].…”
Section: Background Idea Generation Methodsmentioning
confidence: 99%
“…These include generative design tools, data-driven approaches, and artificial intelligence (AI) tools such as ChatGPT and Google Bard [19]. Generative design tools use algorithms to generate a large number of design options, which are based on predefined rules and constraints [20]. Data-driven approaches use user data and feedback to guide ideation and design decisions [21].…”
Section: Background Idea Generation Methodsmentioning
confidence: 99%
“…• Interactive knowledge elicitation [70], combining prior knowledge from cognitive science with learning from data [71], and generative user models [72] can support more effective interactions between user and machine.…”
Section: Directionsmentioning
confidence: 99%
“…The current study addressed several gaps in the existing literature on technology adoption. Firstly, previous research has primarily focused on examining the industry changes brought about by GenAI and the feasibility of its rational use in the art and design sectors [3], [4]. However, this study performed an empirical examination by investigating 326 participants' intention to use GenAI, expanding the literature related to GenAI.…”
Section: B Contributionsmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial impact of AI across various design stages and industries. For instance, researchers have proposed an artificial intelligence-aided design framework (AIAD) to optimize the design process and enhance designers' creative abilities [3]. Additionally, [4] has shown that AI can assist application designers with their design work.…”
Section: Introductionmentioning
confidence: 99%